Financial Inclusion and Sharia Financial Literacy Effects on MSME Performance - Syafrizal, Said Herry; Marjulin (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Many MSMEs in Central Aceh Regency do not yet have business licenses, resulting in limited access to formal financing, while the understanding of Sharia finance remains low and hinders optimal financial management. This study aims to explore the effects of financial inclusion and Islamic financial literacy on MSME performance. A quantitative approach was employed in this study, with data collected through questionnaires distributed directly to 40 MSME owners, ensuring that the information obtained reflects the actual experiences and business practices of the respondents. After the data was collected, analysis was performed using multiple linear regression. The results show that financial inclusion and Sharia financial literacy have a positive and significant effect on MSME performance, both partially and simultaneously, emphasizing the importance of expanding access to Sharia-based financial services and increasing Sharia financial literacy, implementing appropriate Sharia financial practices, and providing business assistance to MSMEs to strengthen their competitiveness and sustainability, as well as serving as a guide for policymakers and financial institutions.